Long-term Surgical Outcomes for Vertical Deviations in Thyroid Eye Disease. (3rd April 2017) - Barker, Lucy; Mackenzie, Kelly; Adams, Gill GW; Hancox, Joanne
ABSTRACT: Introduction : Vertical deviations in thyroid eye disease (TED) can present a surgical challenge due to the difficulty and unpredictability of surgery and the high risk of postoperative drift towards overcorrection. This study reports the postoperative outcomes of patients who underwent adjustable vertical strabismus surgery with Vicryl sutures for thyroid eye disease. Methods : We reviewed the records of patients seen for vertical TED strabismus surgery from January 2005 through December 2009. Clinical details were recorded preoperatively, post-adjustment, and at 3 weeks, 3 months, and 1 year postoperatively. Results : The study included 42 patients. Mean age was 62.4 years and 70% were female. All patients were diplopic preoperatively. The mean near vertical deviation was 21.1 prism diopters (PD) preoperatively, 4.0 PD at 3 weeks postoperatively, 5.0 PD at 3 months, and 4.4 PD at 1 year (all mean results representing undercorrection). 71.4% were free of diplopia postoperatively. Seven patients required further surgery, 2 patients needed further botulinum toxin A. Eight patients experienced an overcorrection; five at 3 weeks, seven at 3 months, and eight at 1 year. There was a significant difference in the mean near angle at tie-off post-adjustment in the patients that overcorrected compared to those that did not reverse (3.1 PD vs 7.1 PD; P =0.005). Discussion : Adjustable surgery for vertical strabismus in thyroid eye disease may result in late overcorrection and the need for further intervention. We propose that aiming for an immediate post-adjustment angle of 8 PD undercorrection for near would allow for postoperative drift and reduce the chances of a late overcorrection. This would require careful preoperative counseling of the patient in order to explain that immediate undercorrection and persistent diplopia were necessary in order to generate a better long-term result.